Albumin treatment regimen for type 1 hepatorenal syndrome: a dose–response meta-analysis - Salerno, Francesco (BMC Gastroenterol, 2015)
BACKGROUND: Recommended treatment for type 1 hepatorenal syndrome consists of albumin and vasoconstrictor. The optimal albumin dose remains poorly characterized. This meta-analysis aimed to determine the impact of albumin dose on treatment outcomes. METHODS: Clinical studies of type 1 hepatorenal syndrome treatment with albumin and vasoconstrictor were sought. Search terms included: hepatorenal syndrome; albumin; vasoconstrictor; terlipressin; midodrine; octreotide; noradrenaline; and norepinephrine. A meta-analysis was performed of hepatorenal syndrome reversal and survival in relation to albumin dose. RESULTS: Nineteen clinical studies with 574 total patients were included, comprising 8 randomized controlled trials, 8 prospective studies and 3 retrospective studies. The pooled percentage of patients achieving hepatorenal syndrome reversal was 49.5 % (95 % confidence interval, 40.0-59.1 %). Increments of 100 g in cumulative albumin dose were accompanied by significantly increased survival (hazard ratio, 1.15; 95 % confidence interval, 1.02-1.31; p = 0.023). A non-significant increase of similar magnitude in hepatorenal syndrome reversal was also observed (odds ratio, 1.15; 95 % confidence interval, 0.97-1.37; p = 0.10). Expected survival rates at 30 days among patients receiving cumulative albumin doses of 200, 400 and 600 g were 43.2 % (95 % confidence interval, 36.4-51.3 %), 51.4 % (95 % confidence interval, 46.3-57.1 %) and 59.0 % (95 % confidence interval, 51.9-67.2), respectively. Neither survival nor hepatorenal syndrome reversal was significantly affected by vasoconstrictor dose or type, treatment duration, age, baseline serum creatinine, bilirubin or albumin, baseline mean arterial pressure, or study design, size or time period. CONCLUSIONS: This meta-analysis suggests a dose–response relationship between infused albumin and survival in patients with type 1 hepatorenal syndrome. The meta-analysis provides the best current evidence on the potential role of albumin dose selection in improving outcomes of treatment for type 1 HRS and furnishes guidance for the design of future dose-ranging studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12876-015-0389-9) contains supplementary material, which is available to authorized users.